ACTIVATING RECEPTIVE VOCABULARY IN EFL SPEAKING THROUGH TECHNOLOGY-MEDIATED INSTRUCTION (Eureka Journal of Language, Culture & Social Change, 2026)
The gap between receptive and productive vocabulary knowledge remains a persistent challenge in English as a Foreign Language (EFL) speaking, particularly in contexts where learners have limited opportunities for authentic oral interaction. Although university learners often demonstrate substantial receptive vocabulary knowledge through reading and listening, they frequently struggle to retrieve and use this knowledge during spontaneous spoken communication. Recent advances in educational technology have been suggested as a means of facilitating lexical activation by providing increased opportunities for output, interaction, and feedback. However, empirical research examining how technology-mediated strategies specifically support the transformation of receptive vocabulary into productive spoken use remains limited, especially in underrepresented EFL contexts.
Keywords: productive vocabulary, receptive vocabulary, EFL speaking, technology-mediated language learning, vocabulary activation, mobile-assisted language learning, university EFL learners.